THE CETAK SAWAH RAKYAT PROGRAM: EFFORTS TO INCREASE RICE PRODUCTION IN THE ARCHIPELAGIC REGION OF SALANG DISTRICT, SIMEULUE REGENCY - Aswin Nasution; Wira Hadianto; Abdul Latif; Yusrizal; Izwar; Hartini; Sri Handayani; Sufriadi; Teuku Muhammad Syauqi; Agustiar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The Cetak Sawah Rakyat (CSR) program conceptually executed as a paddy field optimization initiative is a government strategy aimed at increasing rice production and strengthening food security by enhancing land productivity and cropping intensity. As an archipelagic region, Simeulue Regency possesses significant potential for rice field development; however, it faces various constraints, such as limited agricultural infrastructure and cultivation technology, which restrict optimal cropping frequency. This community service activity was conducted to enhance farmers' understanding and readiness regarding the implementation of the CSR Program in Simeulue Regency. Held at the Agricultural Extension Center (BPP) office in Salang District, the activity employed a participatory empowerment approach involving farmers, farmer groups, village governments, agricultural extension officers (PPL), and the Department of Agriculture of Simeulue Regency. The methods comprised preparatory stages, socialization and counseling, problem identification discussions, and the distribution of questionnaires to assess farmer group readiness. Of the 1,162 hectares of land proposed under the prospective farmer and land scheme (CPCL), 981.36 hectares met the technical and administrative requirements, with 31 farmer groups declared eligible for the program. This community service initiative successfully enhanced public understanding regarding their rights, obligations, and the importance of sustainable rice field management. The CSR program is expected to boost rice production by increasing annual harvest frequency, strengthen institutional capacity among farmers, increase community income, and support sustainable food security in archipelagic regions.